Optimasi Model Persediaan Produk Makanan Ternak Pada Tingkat Distributor di Propinsi Daerah Istimewa Yogyakarta - Kuncoro Harto Widodo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Inventory management is a general problem in manufactures, service companies, government institutions included feedmill distributor. Inventory policy in those institutions are determined by several objectives which the main are minimizing the total cost or investment inventory, the consumer satisfaction and maximizing the output efficiency. Structural problems related with feedmill inventory consists of total cost inventory, order quantity and reorder point. Economic Order Quantity (EOQ) model is one of tools in order to solve problems above, in detail this tool is used to optimize feedmill inventory in the distributor level, especially in the feedmill manufacturing product, the milled corn and the rice sifting components. The result of the research shows that by using the EOQ model, there is a total cost inventory reduction, such as the feedmill manufacturing product decrease from 8,046,778 rupiahs to 1,890,865 rupiahs, the milled corn component from 1,785,721 rupiahs to 103,310 rupiahs and total cost inventory for the rice siftings component decrease from 598,812 rupiahs to 96,686 rupiahs. Based on the final result above, it is summarized that the EOQ model instrument minimized the total cost inventory in feedmill product on the distributor level.